Evaluating Bank Cost Efficiency Using Stochastic Frontier Analysis - Abel, Sanderson; Bara, Alex; Roux, Pierre Le (Journal of Economics and Behavioral Studies, 2019)
The study seeks to assess the cost efficiency of the commercial banks in Zimbabwe using the stochastic frontier analysis. The cost efficiency of the Zimbabwean banks is estimated using the trans-log stochastic frontier approach. The Stochastic Frontier Analysis methodology is among the host of methods that has been used to measure banking sector efficiency. The analysis of cost efficiency of commercial banks has important implications for the economy since an efficient banking system has potential to reduce interest rates which can lead to increased investment and growth for the economy. The cost of doing business in Zimbabwe is perceived to be high hence improved bank efficiency has the potential to reduce the cost of doing business. The average cost efficiency scores for the Zimbabwean banks over the study period show that the banking sector in Zimbabwe experiencing 17 percent inefficiency. The efficiency levels have been declining over the years reflecting increased resource wastage in the system. The study recommends that the banking institutions should continue to innovate so as to reduce their inefficiencies.